Analisis Penetapan Harga Terhadap Keputusan Pembelian Konsumen - Victorinus Laoli; Fatolosa Hulu (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2018)
This study aims to know to know and analyze the pricing of purchasing decisions on UD. Sentosa Gunungsitoli. Population determination in this study is as many as 450 people per day. With average visitor details of 15 people per day multiplied by one month (30 days). The sample to be taken is 10% of 450 people that is 45 people. Sample collection method used is stratified random sampling (random sampling study). Researchers use Likert scale as a measuring tool. From result of calculation of correlation coefficient between variable X (price determination) influence to variable Y (decision of purchase) obtained rhitung (rxy) = 0,818 if consulted at price critics table r product moment for 5% confidence interval after counting it r count = 0,818> from rtabel = 0,514. Thus it can be concluded that there is a strong or positive influence between the pricing of purchasing decisions on building materials at UD. Sentosa Gunungsitoli. The contribution of working price determination to purchase decision is = 66,91%.